Madonna and Child - Stone, George Eathl (photographer):::Creator::::::::::::
Photograph of an Italian Sculpture of the Virgin and Child sitting within an ancient Roman-style alcove with the inscription at the base: "AVE MARIA, " by Andrea della Robbia, 1435 - 1525.